2008
DOI: 10.1007/s11548-008-0275-9
|View full text |Cite
|
Sign up to set email alerts
|

Generation of three-dimensional prototype models based on cone beam computed tomography

Abstract: Purpose The purpose of this study was to generate threedimensional models based on digital volumetric data that can be used in basic and advanced education. Methods Four sets of digital volumetric data were established by cone beam computed tomography (CBCT) (Accuitomo, J. Morita, Kyoto, Japan). Datasets were exported as Dicom formats and imported into Mimics and Magic software programs to separate the different tissues such as nerve, tooth and bone. These data were transferred to a Polyjet 3D Printing machine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 17 publications
(14 reference statements)
0
24
0
3
Order By: Relevance
“…The models were therefore assessed as being suitable for surgical planning, and surgery was performed accordingly. In 2009 Lambrecht et al [7] published their workflow for 3D model fabrication based on CBCT datasets; however, the authors concluded that automated routine fabrication was too time-consuming and expensive [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The models were therefore assessed as being suitable for surgical planning, and surgery was performed accordingly. In 2009 Lambrecht et al [7] published their workflow for 3D model fabrication based on CBCT datasets; however, the authors concluded that automated routine fabrication was too time-consuming and expensive [7].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 Lambrecht et al [7] published their basic workflow for the production of CBCT-based 3D models, which was modified slightly in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients and medical trainees and residents can benefit from 3D printed models [26,98]. High maintenance charges, cultural and social complications, and formalin-related safety issues are making cadavers a limited source for medical education [99,100].…”
Section: Surgical Educationmentioning
confidence: 99%
“…[22] and [23] rapid tooling (RT) [24] and machining [25] are currently used to fabricate dental models. These models help a surgeon to diagnose, plan a treatment [26] and [27] and perform surgery [28] and [29].…”
Section: Introductionmentioning
confidence: 99%